Practice patterns in the management of preterm labor in India: a multi-centric, retrospective study - Jaju, P. B.; Sood, Abha; Chavan, Vaishali; Devgarha, Geetanjali; Jain, Seema; Kundapur, Vinodraj; Hegde, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm labor (PTL) is considered as one of the leading cause of perinatal morbidity and mortality. Preterm labor refers to the onset of uterine contractions of sufficient strength and frequency to effect progressive dilatation and effacement of cervix between 22 and 37 weeks of gestation. Methods: In this study, 285 patients of PTL admitted/treated (during the period of 1st January 2014 to 31st December 2016) across 5 centres in India were enrolled. Adult women with PTL, receiving oral or intravenous regime of tocolytic drugs were screened based on eligibility criteria. Results: We evaluated the practice patterns in the management of PTL in India. The pharmacological management (n=193) was preferred over nonpharmacological management (n=92) in the present study. Amongst the pharmacological agents, isoxsuprine (60.10%) was more frequently used followed by nifedipine (23.83%). Prolongation of delivery for at least 48 hours was observed in 57.76% patients receiving isoxsuprine compared to 34.78% patients receiving nifedipine. The mean latency period (36.77±28.09 vs. 1.44±1.33 days), birthweight (2.25±1.34 vs. 1.07±0.34 kg) and Apgar score at 5 mins (7.56±2.36 vs. 4.87±2.10) was higher for isoxsuprine compared to nifedipine group patients, with mean gestational age of <32 weeks (extreme to very PTL cases; p<0.0001). Similar results were observed in latency period and Apgar score between isoxsuprine and nifedipine groups in late PTL cases (>32 weeks). Conclusions: Pharmacological treatment was preferred for the management of PTL in India. Among pharmacological agents, isoxsuprine was preferred over other tocolytics. Significant improvement in mean latency period, prolongation of delivery beyond 48 hours and perinatal outcomes were noted amongst patients on isoxsuprine versus other pharmacological agents.